Level: Standard
2) Given: -2(x - 4) = 3(x + 12); Prove: x = -5.6
Statements
Reasons
![Level Standard 2 Given 2x 4 3x 12 Prove x 56 Statements Reasons class=](https://us-static.z-dn.net/files/d73/7be795580cace3f27001cd543d428ade.png)
Answer:
Step-by-step explanation:
-2(x - 4) = 3(x + 12) {Use distributive rule}
-2*x - 4 *(-2) = 3*x + 12*3
-2x + 8 = 3x + 36 {add 2x to both sides}
8 = 3x + 36 +2x
8 = 5x + 36
8 - 36 = 5x {subtract 36 from both sides}
-28 = 5x
5x = -28 {Divide both sides by 5}
x = -28/5
x = -5.6